Brahmi inscription on the pillar in the antarala - Temples of India Project Team (Jio Institute, 2024)
The pillar on the north end of the antarala has an inscription in Brahmi script with Gupta letters playing an important role in dating the foundation of the temple. The inscription is carved below a full-blown lotus. However, the surface of the pillar has deteriorated and the letters are not clear, making it difficult to discern the meaning of the inscription. Nevertheless, one can observe that the inscription comprises twelve lines. The last three lines appear distinct in their letters and style compared to the upper part of the inscription. The first three lines of the inscription discuss the Shiva linga and the temple.